2016
DOI: 10.1163/15699846-01601003
|View full text |Cite
|
Sign up to set email alerts
|

Subject-Verb Agreement with Coordinated Subjects in Ancient Greek

Abstract: In Ancient Greek, as well as in other languages, whenever agreement is triggered by two or more coordinated phrases, two different constructions are allowed: either the agreement can be controlled by the coordinated phrase as a whole, or it can be triggered by just one of the coordinated words. In spite of the amount of information that can be read on this topic in grammars of Ancient Greek, much is still to be known even at a general descriptive level. More importantly, the data still lack a convincing explan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Smyth 1920: 265;Kühner, Raphael & Bernard Gerth 1898: 77-82. 4 On the subject, see now the treebank-based analysis of Mambrini & Passarotti 2016. 5 Mambrini & Passarotti 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Smyth 1920: 265;Kühner, Raphael & Bernard Gerth 1898: 77-82. 4 On the subject, see now the treebank-based analysis of Mambrini & Passarotti 2016. 5 Mambrini & Passarotti 2012.…”
Section: Discussionmentioning
confidence: 99%
“…Treebanks such as the ones presented here are a resource for the application of these methods. For example, Greek copular verbs and subject-verb agreement have recently been studied on the basis of annotated dependency data [10,11]. McGillivray and Vatri [12] use treebanks to examine the relationship of acoustic and syntactic information.…”
mentioning
confidence: 99%
“…Closest-conjunct agreement with VS and SV (without any intervening element between the subject and the verb) in Plato ..among whom are Hesiod and Archilochus.' (Plato, Ion 532a)Johnson (2013), in a contrastive study of Latin and Greek,Lavidas (2014a), in a study on language change, andMambrini and Passarotti (2016), in a corpus study of Ancient Greek, have also offered valuable data on partial agreement in Classical Greek Mambrini and Passarotti (2016). have shown that closest-conjunct agreement, rather than full agreement, is dominant in Ancient Greek (in the case of conjoined subjects) and that there are very few cases in their Ancient Greek data where the furthest conjunct triggers partial agreement.68 Eumelos.GEN back.NOM.SG broad-PTC shoulder.NOM.DU thérmet' make-hot.IMPF.3SG.MP 'and the breadth of them was hot on the back and on the broad shoulders of Eumelos'(Homer, Iliad 23.380) …”
mentioning
confidence: 99%
“…Mambrini and Passarotti's (2016) data concern all cases of conjoined subjects (and not only examples with verbs in the indicative mood and without any intervening element between the subject, the object and the verb), and, regarding Plato, the data only concern the text of "Euthyphro".…”
mentioning
confidence: 99%